2017
DOI: 10.1089/cyber.2016.0402
|View full text |Cite
|
Sign up to set email alerts
|

Ideological Consumerism in Colombian Elections, 2015: Links Between Political Ideology, Twitter Activity, and Electoral Results

Abstract: Propagation of political ideologies in social networks has shown a substantial impact on voting behavior. Both the contents of the messages (the ideology) and the politicians' influence on their online audiences (their followers) have been associated with such an impact. In this study we evaluate which of these factors exerted a major role in deciding electoral results of the 2015 Colombian regional elections by evaluating the linguistic similarity of political ideologies and their influence on the Twitter sph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
0
11
0
3
Order By: Relevance
“…Although there have been cases of Zika in English-speaking countries, the epidemic primarily affected Latin American countries, particularly Brazil. The threat and uncertainty produced by the virus might therefore have been much stronger and more visible in Portuguese or Spanish messages, and future research on Zika rumors could compare how these ideas spread across cultural, national, and linguistic boundaries (with the necessary care taken to use appropriate data pre-processing 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been cases of Zika in English-speaking countries, the epidemic primarily affected Latin American countries, particularly Brazil. The threat and uncertainty produced by the virus might therefore have been much stronger and more visible in Portuguese or Spanish messages, and future research on Zika rumors could compare how these ideas spread across cultural, national, and linguistic boundaries (with the necessary care taken to use appropriate data pre-processing 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Colombians had the chance to know the terms of this agreement before deciding to support or reject its implementation in a referendum held on October 2, 2016. The political abstention in this plebiscite was 62.57% of the electorate, one of the greatest compared with previous elections (Correa & Camargo, 2017). The proposed implementation was officially rejected by 18.44% of the electorate.…”
mentioning
confidence: 78%
“…This is a novel path that shows how politicians are employing Twitter for political purposes through the impact of retweets. Despite the existence of similar efforts done in Europe [12,14], Asia [13], North America [16,17] or more developed countries [18], we are not aware of similar works done in South America, except for those of Correa and Camargo [19]. Our approach complements others that focus on the use of Twitter in Colombia without tackling the issue of retweets [45].…”
Section: Discussionmentioning
confidence: 99%
“…This relates with the so-called ‘ideological consumerism’, which entails the links between political ideology, Twitter activity and electoral results. A recent study showed that in the last Colombian regional elections, electoral results showed to be more strongly associated with the amount of retweets and original tweets than with the similarity of ideological contents or the number of Twitter followers [19]. These results shed light on the importance of improving our understanding of the relationship between tweeting short messages for political campaigns and identifying which contents are more likely of being retweeted.…”
Section: Introductionmentioning
confidence: 96%